Composite catalyst as well as preparation method and application thereof

By using a composite catalyst composed of nanocarbides, nanooxides and alkali metal single atoms, a sandwich-like structure is formed, which solves the problem that existing catalysts can effectively catalyze the cyclization reaction between CO2 and 2-aminobenzonitrile under high pressure, and achieves efficient catalytic preparation of nitrogen-containing heterocyclic compounds under normal pressure, which meets the requirements of green chemistry.

CN119869573APending Publication Date: 2025-04-25BEIJING UNIV OF CHEM TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411982933.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-25

AI Technical Summary

Technical Problem

The existing heterogeneous catalysts can effectively catalyze the cyclization reaction between CO2 and 2-aminobenzidine under high pressure conditions, and it is difficult to achieve efficient catalysis under normal pressure.

Method used

A composite catalyst is used, which consists of nanocarbides, nanooxides and alkali metal single atoms to form a sandwich-like structure. By regulating the crystal state of the metal oxide and the active site of the carbide support, the efficient activation and reaction of CO2 and nitrile raw materials can be achieved.

Benefits of technology

It has achieved efficient catalytic preparation of nitrogen-containing heterocyclic compounds, especially quinazolinone compounds under normal pressure, which has improved the selectivity and yield of the reaction, reduced costs, and is in line with the concept of green chemistry and sustainable development.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869573A_ABST
    Figure CN119869573A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of catalysis, and particularly relates to a composite catalyst and a preparation method and application thereof. The composite catalyst provided by the invention has a sandwich-like laminated structure, effectively regulates and controls the crystal state of the metal oxide, modifies the active site of the carbide carrier, realizes the synergistic activation of CO2 and nitrile raw materials by the multifunctional active site of the catalyst, optimizes the adsorption and desorption of various reaction intermediates, improves the selectivity of the reaction, and reduces the production cost. The reaction is promoted to realize high-efficiency conversion to the target product quinazolinone under the normal pressure condition without adding an organic micromolecule cocatalyst, and the conversion rate is high. The composite catalyst provided by the invention can efficiently catalyze and prepare the nitrogen-containing heterocyclic ring compound at normal pressure, and is low in cost, green, environment-friendly and easy to separate. The composite catalyst provided by the invention is high in catalytic efficiency and mild in catalytic condition, keeps high selectivity and high conversion rate, and does not need an ammonia functionalization auxiliary agent.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of catalysis, and in particular relates to a composite catalyst and a preparation method and application thereof. Background Art

[0002] Nitrogen-containing heterocyclic compounds have good biocompatibility and are often used as the core structure of biologically active molecules or drug molecules. Among them, quinazolinone compounds are widely used in medicinal chemistry and have pharmacological activities such as anti-tumor, anti-inflammatory, antibacterial, antimalarial, antihypertensive and sedative. Converting CO2 into high-value-added fine chemicals and pharmaceutical intermediates through chemical fixation is an effective way to achieve carbon cycle. In view of this, the development of green, precise and efficient direct preparation of quinazolinone compounds using CO2 as a synthon and coupling with 2-aminobenzonitrile compounds is not only an important green chemical approach to achieve carbon cycle, but also has important significance for the development of life chemistry.

[0003] The cyano group (-CN) in nitrile has a strong chemical bond energy, which leads to its high stability. It is difficult to activate under mild conditions and is generally catalyzed by a heterogeneous catalyst. However, most of the heterogeneous catalysts currently developed must be used under high pressure conditions. For example, heterogeneous catalysts such as MCM-41 and TBD@Fe3O4 catalyze the cyclization reaction of CO2 and 2-aminobenzonitrile to prepare quinazolinone. The catalytic system contains amino substances as auxiliary functional groups, and the reaction must be carried out under 3.5-4MPa pressure conditions. Summary of the invention

[0004] The purpose of the present invention is to provide a composite catalyst and a preparation method and application thereof. The composite catalyst provided by the present invention can catalyze and prepare nitrogen-containing heterocyclic compounds at normal pressure with high efficiency.

[0005] In order to achieve the above object, the present invention provides the following technical solutions:

[0006] The invention provides a composite catalyst, comprising nano carbide, nano oxide and alkali metal single atom; the nano carbide and nano oxide form a composite; the nano carbide is a transition metal nano carbide; the alkali metal single atom is loaded on the composite; the nano carbide, nano oxide and alkali metal single atom are stacked in sequence to form a sandwich-like structure.

[0007] Preferably, the transition metal nanocarbide is niobium-based carbide.

[0008] Preferably, the nano-oxide includes crystalline nano-oxide or amorphous nano-oxide.

[0009] Preferably, the alkali metal single atom includes one or more of Na, K, Rb and Cs.

[0010] Preferably, the mass ratio of the nano-oxide to the nano-carbide is 1 to 50:100; the mass ratio of the alkali metal single atom to the nano-carbide is 0.1 to 30:100.

[0011] Preferably, the composite catalyst is a two-dimensional porous nanosheet structure.

[0012] The present invention also provides a method for preparing the composite catalyst described in the above scheme, comprising the following steps:

[0013] The nano-carbide, nano-oxide, alkali metal salt and dispersion medium are mixed, evaporated to dryness and calcined in sequence to obtain the composite catalyst.

[0014] Preferably, the calcination is carried out in an inert atmosphere; the calcination is programmed temperature calcination or constant temperature calcination; the temperature of the constant temperature calcination is 100-500°C, and the insulation calcination time is 1-12h; the programmed temperature calcination includes a first calcination, a second calcination and a third calcination in sequence; the temperature of the first calcination is 200-300°C, and the insulation calcination time is 0.5-1.5h; the temperature of the second calcination is 340-380°C, and the insulation calcination time is 1-3h; the temperature of the third calcination is 430-480°C, and the insulation calcination time is 1-3h.

[0015] The present invention also provides the use of the composite catalyst described in the above scheme or the composite catalyst obtained by the preparation method described in the above scheme in catalytic preparation of nitrogen-containing heterocyclic compounds.

[0016] Preferably, the nitrogen-containing heterocyclic compound is a nitrogen heterocyclic quinazolinone compound.

[0017] The present invention provides a composite catalyst. The composite catalyst provided by the present invention has a sandwich-like stacked structure, utilizes transition metal carbides to activate reaction substrates, utilizes nano-oxides to activate reaction substrates for deprotonation, and alkali metals form single atoms in a highly dispersed state, greatly reducing the amount of metal used, and maximizing the use of metal active sites, while unsaturated coordination and alkali metal single atoms with large ionic radius are used for dynamic adsorption and dissociation of various intermediates, thereby improving the selectivity and yield of the reaction. The present invention realizes the coordinated activation of CO2 and nitrile raw materials by the multifunctional active sites of the catalyst by effectively regulating the crystal state of the metal oxide and modifying the active sites of the carbide carrier, optimizes the adsorption and desorption of various reaction intermediates, improves the selectivity of the reaction, and promotes the reaction under normal pressure conditions without adding organic small molecule co-catalysts, and realizes high-efficiency conversion to the target product quinazolinone, with high conversion rate. The composite catalyst provided by the present invention can efficiently catalyze and prepare nitrogen-containing heterocyclic compounds at normal pressure, and has low cost, is green and environmentally friendly, and is easy to separate.

[0018] The present invention also provides a method for preparing the composite catalyst of the above scheme. The present invention obtains a sandwich-like structure through specific synthesis steps and calcination. The preparation method provided by the present invention has simple steps, readily available raw materials, and convenient operation.

[0019] The present invention also provides the use of the composite catalyst described in the above scheme or the composite catalyst obtained by the preparation method described in the above scheme in the catalytic preparation of nitrogen-containing heterocyclic compounds. The composite catalyst provided by the present invention can catalyze and prepare nitrogen-containing heterocyclic compounds, especially quinazolinone compounds, at normal pressure and with high efficiency, and in particular catalyze the cyclization of CO2 and 2-aminobenzonitrile compounds to prepare quinazolinone compounds with a drug molecule mother core structure. The composite catalyst provided by the present invention has high catalytic efficiency, mild catalytic conditions, and maintains high selectivity and high conversion rate, greatly reducing the economic cost of the reaction, improving production safety, complying with the concepts of green chemistry and sustainable development, and does not require an ammonia functionalized auxiliary agent, which can avoid the attenuation of catalyst performance caused by the loss of amino species, and has the potential for large-scale industrial application. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0021] Figure 1 X-ray diffraction pattern (a) and transmission electron microscope image (b) of Nb2AlC raw material;

[0022] Figure 2 The X-ray diffraction pattern of the composite catalyst (Cs1 / a-MgO / NbC) of Example 1, and the control is NbC nanosheets and crystalline MgO (c-MgO) nanosheets;

[0023] Figure 3 is a transmission electron microscope image of Example 1Cs1 / a-MgO / NbC;

[0024] Figure 4 The spherical aberration corrected electron microscope image and element distribution linear scanning image of Example 1 Cs1 / a-MgO / NbC; wherein, (a) spherical aberration corrected scanning transmission electron microscope image, (b) Fourier transform color image, (c, d) Fourier transform linear fitting image of the atomic distance in (a), (e) element distribution linear scanning image in the scanning transmission electron microscope;

[0025] Figure 5 This is a high-resolution transmission electron microscopy image of Cs1 / a-MgO / NbC in Example 1;

[0026] Figure 6 It is the X-ray diffraction pattern of the composite catalyst (Cs1 / c-MgO / NbC) of comparative example 1, and the control is NbC nanosheet and crystalline MgO (c-MgO) nanosheet;

[0027] Figure 7 This is the high-resolution transmission electron microscopy image of comparative example 1Cs1 / c-MgO / NbC;

[0028] Figure 8 is the X-ray diffraction pattern of the Na1 / -a-MgO / NbC catalyst of Comparative Example 2;

[0029] Fig. 9 is the X-ray diffraction pattern of comparative example 3K1 / -a-MgO / NbC catalyst;

[0030] Fig.10 is the X-ray diffraction pattern of the comparative example 5a-MgO / NbC catalyst;

[0031] Fig.11 This is the X-ray diffraction pattern of the comparative example 6Cs1 / NbC catalyst. DETAILED DESCRIPTION

[0032] The invention provides a composite catalyst, comprising nano carbide, nano oxide and alkali metal single atom; the nano carbide and nano oxide form a composite; the nano carbide is a transition metal nano carbide; the alkali metal single atom is loaded on the composite; the nano carbide, nano oxide and alkali metal single atom are stacked in sequence to form a sandwich-like structure.

[0033] In the present invention, the transition metal nanocarbide is preferably a niobium-based carbide; the niobium-based carbide is preferably a niobium carbide (NbC) nanosheet. The present invention uses nanocarbide as a substrate material of a sandwich-like structure. The nanocarbide in the present invention belongs to a metal intercalation compound, has a noble metal-like property, and is helpful for efficiently activating small organic molecules.

[0034] In the present invention, the method for preparing the niobium carbide nanosheets is preferably: Nb2AlC powder is immersed in a hydrofluoric acid solution for etching and then intercalated and stripped in an ammonium salt solution.

[0035] In the present invention, the concentration of the hydrofluoric acid solution is preferably 35-60wt%, specifically 60wt%; the mass volume ratio of the Nb2AlC powder and the hydrofluoric acid solution is preferably (1-10)g:(20-70)mL, specifically 5g:50mL.

[0036] In the present invention, the immersion time is preferably not less than 3 days, specifically 0.5 days, 1 day, 2 days or 3 days; the immersion is preferably carried out under stirring conditions.

[0037] In the present invention, the impregnation preferably further includes neutralizing the obtained product dispersion; the neutralization is preferably: centrifuging the obtained product dispersion to neutrality with a polar solvent; the polar solvent preferably includes one or both of deionized water and ethanol.

[0038] In the present invention, the ammonium salt in the ammonium salt solution preferably includes one or more of tetramethylammonium hydroxide, tetrapropylammonium hydroxide and tetrabutylammonium hydroxide; the concentration of the ammonium salt solution is preferably 25wt%; the mass volume ratio of the Nb2AlC powder and the ammonium salt solution is preferably (1-10)g:(20-80)mL, specifically 5g:60mL.

[0039] In the present invention, the intercalation stripping time is preferably not less than 18 hours, and specifically can be 18 hours, 20 hours, 26 hours, 32 hours or 48 hours.

[0040] In the present invention, after the intercalation stripping, the obtained product system is preferably subjected to centrifugal washing, solid-liquid separation and drying in sequence; the washing reagent is preferably a polar solvent; the polar solvent preferably includes one or both of deionized water and ethanol; the solid-liquid separation is preferably suction filtration. The niobium carbide prepared by the present invention presents a single-layer two-dimensional nanosheet morphology.

[0041] In the present invention, the nano-oxide preferably includes crystalline nano-oxide or amorphous nano-oxide; the crystalline oxide or amorphous oxide is preferably alkaline earth metal nano-oxide; the alkaline earth metal nano-oxide is preferably magnesium oxide (MgO) nano-sheet.

[0042] In the present invention, the preparation method of the magnesium oxide nanosheets is preferably: mixing a magnesium salt and an alkaline solution, and then sequentially performing a hydrothermal reaction, centrifugal washing, drying and calcining; the magnesium salt is preferably Mg(NO3)2·6H2O; the pH value of the alkaline solution is preferably 12 to 14, specifically 13, and the concentration is preferably 0.1 to 1 mol / L, specifically 0.5 mol / L or 0.8 mol / L; the alkaline solution preferably includes a sodium hydroxide solution or a potassium hydroxide solution; the mass volume ratio of the magnesium salt and the alkaline solution is preferably 1g:(10 to 30)mL, specifically 1g:30mL, 1g:15mL or 1g:10mL; the mixing is preferably stirring.

[0043] In the present invention, the hydrothermal reaction is preferably constant temperature hydrothermal; the temperature of the hydrothermal reaction is preferably 60-100°C, specifically 60°C, 70°C, 80°C, 90°C or 100°C; the time of the hydrothermal reaction is preferably 2-4h, specifically 2h, 2.5h, 3h, 3.5h or 4h; the calcination is preferably programmed temperature calcination; the temperature program of the programmed temperature calcination preferably includes sequentially performing a first calcination, a second calcination and a third calcination; the temperature of the first calcination is preferably 200-300°C, specifically 240°C or 250°C. The temperature of the second calcination is preferably 340-380°C, specifically 350°C, 360°C or 370°C, and the calcination time is preferably 1-3h, specifically 1.5h, 2h or 2.5h; the temperature of the third calcination is preferably 430-480°C, specifically 440°C, 450°C, 460°C or 470°C, and the calcination time is preferably 1-3h, specifically 1.5h, 2h or 2.5h.

[0044] In the present invention, the mass ratio of the nano oxide to the nano carbide is preferably 1-50:100, specifically 1:100, 3:100, 5:100, 8:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100 or 50:100.

[0045] In the present invention, the alkali metal single atom preferably includes one or more of Na, K, Rb and Cs, and more preferably Cs. The present invention uses Cs, which is more conducive to improving catalytic selectivity and reaction yield.

[0046] In the present invention, the mass ratio of the alkali metal single atom to the nanocarbide is preferably 0.1-30:100, specifically 0.1:100, 0.2:100, 0.3:100, 0.5:100, 0.7:100, 1:100, 3:100, 5:100, 7:100, 10:100, 12:100, 15:100, 20:100, 22:100, 25:100, 27:100 or 30:100.

[0047] In the present invention, the composite catalyst is preferably a two-dimensional porous nanosheet structure. The composite catalyst provided by the present invention is a two-dimensional porous nanosheet structure, and the two-dimensional nanosheet has a large specific surface area, which is conducive to exposing more catalytic active sites; the porous structure is conducive to heat transfer, mass transfer and promoting the adsorption-desorption of intermediates and products, inhibiting side reactions, and improving the selectivity of the reaction and the yield of the target product.

[0048] The present invention also provides a method for preparing the composite catalyst described in the above scheme, comprising the following steps:

[0049] The nano-carbide, nano-oxide, alkali metal salt and dispersion medium are mixed, evaporated to dryness and calcined in sequence to obtain the composite catalyst.

[0050] The present invention mixes nanocarbides, nanooxides, alkali metal salts and a dispersion medium (referred to as the first mixing) to obtain a three-component dispersion. In the present invention, the mass ratio of the nanooxide to the nanocarbides is preferably 1 to 50:100, specifically 1:100, 3:100, 5:100, 8:100, 10:100, 15:100, 20:100, 25:100, 30:100, 35:100, 40:100, 45:100 or 50:100.

[0051] In the present invention, the alkali metal salt is preferably an alkali metal soluble salt; the alkali metal soluble salt preferably includes one or more of sodium carbonate, potassium carbonate, cesium carbonate and rubidium carbonate.

[0052] In the present invention, the mass ratio of the alkali metal salt to the nanocarbide is preferably 1:50-2, specifically 1:50, 1:25, 33:200 or 83:200.

[0053] In the present invention, the dispersion medium is preferably water; the water is preferably deionized water.

[0054] In the present invention, the mass volume ratio of the nanocarbide and the dispersion medium is preferably (2-15) mg:1 mL, specifically 5 mg:1 mL, 8.5 mg:1 mL or 10 mg:1 mL.

[0055] In the present invention, the first mixing is preferably: dispersing nanocarbides into a part of the dispersion medium to obtain a carrier dispersion; mixing nanooxides and the carrier dispersion (referred to as the second mixing) to obtain a composite solution, and then adding an alkali metal salt and an alkali metal salt solution obtained from the remaining dispersion medium to the composite solution.

[0056] In the present invention, the dispersion is preferably ultrasonic followed by stirring; the second mixing is preferably performed by alternating stirring and ultrasonication; the number of stirring is preferably 2 to 5 times. The present invention uniformly disperses the nano oxide powder in the dispersion medium through the ultrasonic stirring.

[0057] In the present invention, the temperature of the first mixing is preferably 60-90°C, specifically 70°C.

[0058] After obtaining the three-component dispersion, the present invention sequentially evaporates and calcines the three-component dispersion to obtain the composite catalyst. In the present invention, the evaporation temperature is preferably 60-100°C, specifically 60°C, 70°C, 80°C, 90°C or 100°C.

[0059] In the present invention, the calcination is preferably carried out in an inert atmosphere; the inert atmosphere is preferably argon; the calcination is preferably programmed temperature calcination or constant temperature calcination; the temperature of the constant temperature calcination is preferably 100-500°C, specifically 100°C, 150°C, 200°C, 250°C, 300°C, 350°C, 400°C, 450°C or 500°C, and the insulation calcination time is preferably 1-12h, specifically 1h, 2h, 3h, 5h, 7h, 9h, 10h or 12h.

[0060] In the present invention, the programmed temperature calcination preferably includes a first calcination, a second calcination and a third calcination in sequence; the temperature of the first calcination is preferably 200-300°C, specifically 240°C or 270°C, and the insulation calcination time is preferably 0.5-1.5h, specifically 0.8h or 1.2h; the temperature of the second calcination is preferably 340-380°C, specifically 350°C, 360°C or 370°C, and the insulation calcination time is preferably 1-3h, specifically 1.5h, 2h or 2.5h; the temperature of the third calcination is preferably 430-480°C, specifically 440°C, 450°C, 460°C or 470°C, and the insulation calcination time is preferably 1-3h, specifically 1.5h, 2h or 2.5h.

[0061] The present invention also provides the use of the composite catalyst described in the above scheme or the composite catalyst obtained by the preparation method described in the above scheme in catalytic preparation of nitrogen-containing heterocyclic compounds.

[0062] In the present invention, the nitrogen-containing heterocyclic compound is preferably a nitrogen heterocyclic quinazolinone compound.

[0063] In the present invention, the application of the catalytic preparation of nitrogen-containing heterocyclic compounds preferably includes the following steps: mixing reactant molecules, a composite catalyst and a solvent in a carbon dioxide atmosphere to carry out a cyclization reaction to obtain nitrogen-containing heterocyclic compounds; the composite catalyst is the composite catalyst described in the above scheme or the composite catalyst obtained by the preparation method described in the above scheme.

[0064] In the present invention, the reactant molecule is preferably a nitrile compound; the nitrile compound is preferably a 2-aminobenzonitrile compound; the 2-aminobenzonitrile compound preferably includes one or more of 2-aminobenzonitrile, 2-amino-5-fluorobenzonitrile, 2-amino-5-bromobenzonitrile, 2-amino-5-chlorobenzonitrile and 2-amino-4-chlorobenzonitrile.

[0065] In the present invention, the mass ratio of the composite catalyst to the reactant molecules is preferably 1 to 3:1, specifically 1:1, 2:1 or 3:1.

[0066] In the present invention, the solvent is preferably an amide solvent; the amide solvent is preferably N,N-dimethylformamide (DMF).

[0067] In the present invention, the molar volume ratio of the reactant molecules and the solvent is preferably (0.1-5) mmol:(1-6) mL, and can be specifically 0.1 mmol:1 mL, 0.5 mmol:1 mL, 1 mmol:1 mL, 2 mmol:1 mL, 3 mmol:1 mL, 5 mmol:1 mL, 0.1 mmol:3 mL, 0.5 mmol:3 mL, 1 mmol:3 mL, 2 mmol:3 mL, 3 mmol:3 mL, 5 mmol:3 mL, 0.1 mmol:5 mL, 0.5 mmol:5 mL, 1 mmol:5 mL, 2 mmol:5 mL, 3 mmol:5 mL, 5 mmol:5 mL, 0.1 mmol:6 mL, 0.5 mmol:6 mL, 1 mmol:6 mL, 2 mmol:6 mL, 3 mmol:6 mL or 5 mmol:6 mL.

[0068] In the present invention, the carbon dioxide is preferably provided by a normal pressure CO2 balloon.

[0069] In the present invention, the cyclization reaction is preferably carried out in a heterogeneous catalytic system without an auxiliary agent; the temperature of the cyclization reaction is preferably 60-160°C, specifically 60°C, 80°C, 100°C, 120°C, 140°C or 160°C, the pressure is preferably normal pressure, and the insulation reaction time is preferably 8-24h, specifically 8h, 10h, 12h, 16h, 18h, 20h or 24h.

[0070] In the present invention, after the cyclization reaction, the process preferably further comprises removing the composite catalyst from the obtained product system and then washing and drying the composite catalyst in sequence.

[0071] In the present invention, the removal of the composite catalyst is preferably filtration; the washing reagent is preferably a polar reagent; the polar reagent preferably includes one or more of dimethylformamide and dichloromethane; the drying is preferably freeze-drying; the freeze-drying equipment is preferably a centrifugal concentrator or a freeze dryer; the freeze-drying time is preferably 2 to 10 hours, specifically 4 hours or 7 hours.

[0072] A significant advantage of the present invention is that the catalytic reaction is carried out in a normal pressure CO2 atmosphere, which greatly reduces equipment costs, improves safety, simplifies the operation process, and the environmentally friendly normal pressure reaction is more in line with the concept of green chemical synthesis and sustainable development. Another significant advantage of the present invention is that the catalytic reaction is carried out in a heterogeneous catalytic system without adding an organic base co-catalyst, which simplifies the post-processing processes such as separation of the product and the catalyst and product purification.

[0073] In order to further illustrate the present invention, the scheme of the present invention is described in detail below in conjunction with the accompanying drawings and embodiments, but they should not be understood as limiting the protection scope of the present invention.

[0074] Example 1

[0075] This embodiment prepares a Cs1 / a-MgO / NbC sandwich nanocomposite catalyst, and the preparation method steps are as follows:

[0076] (1) 2.0 g of Nb2AlC powder was dispersed in 35 mL of hydrofluoric acid solution (concentration of 60%) and stirred for etching for 3 days. The resulting solution was then centrifuged and washed with deionized water until it was neutral (pH ≈ 7) to obtain a solid. The X-ray diffraction pattern and transmission electron microscopy image of the Nb2AlC raw material are shown in the figure. Figure 1 As shown, it can be seen that there are no impurities in the raw material, which is a micron-sized block solid.

[0077] (2) The solid obtained in step (1) is transferred to 40 mL of 25 wt% tetrabutylammonium hydroxide solution and stirred for 20 h. The mixture is then washed with ethanol and deionized water and filtered. The solid obtained by filtration is transferred to a freeze dryer and freeze-dried into powder to obtain NbC two-dimensional nanosheets.

[0078] (3) 2.0 g of Mg(NO3)2·6H2O powder was added to 0.1 M sodium hydroxide solution (pH 13) and stirred to dissolve, then transferred to a reactor and hydrothermally heated at 80°C for 2 h, then washed with deionized water, dried at 60°C for 8 h, and the product was collected to obtain a powder.

[0079] (4) The powder obtained in step (3) is calcined in an air atmosphere by programmed temperature increase, firstly increasing the temperature to 280° C. and keeping the temperature constant for 1 h, then increasing the temperature to 350° C. and keeping the temperature constant for 2 h, and then increasing the temperature to 450° C. and keeping the temperature constant for 2 h, collecting the product to obtain MgO nanosheets.

[0080] (5) The NbC nanomaterial obtained in step (2) was mixed with 35 mL of deionized water to obtain a NbC dispersion.

[0081] (6) The MgO nanosheets prepared in step (4) and 8 mL of deionized water solvent were mixed to obtain a MgO dispersion, and the MgO dispersion was added to the NbC dispersion prepared in step (5). After stirring and ultrasonic cycling until uniform dispersion, a mixed dispersion of MgO / NbC nanocomposite (the mass ratio of MgO to NbC was 1:10) was obtained.

[0082] (7) Add the cesium carbonate solution to the MgO / NbC mixed dispersion of step (6), transfer to a heating device, heat to 70°C, stir, and then heat to 90°C to evaporate to dryness, to obtain a Cs-MgO-NbC mixed powder (Cs + The mass ratio of Nb to NbC is ~1:20).

[0083] (8) The Cs-MgO-NbC mixed powder obtained in step (7) is placed in argon and subjected to programmed temperature calcination, firstly heated to 280°C and kept at this temperature for 1 h, then heated to 350°C and kept at this temperature for 2 h, and then heated to 450°C and kept at this temperature for 2 h, to obtain a Cs1 / a-MgO / NbC composite catalyst.

[0084] The composite catalyst prepared in this example was subjected to X-ray diffraction analysis, transmission electron microscopy, spherical aberration correction electron microscopy and high-resolution electron microscopy. The X-ray diffraction pattern is as follows: Figure 2 As shown in the transmission electron microscopy image Figure 3 As shown, the spherical aberration corrected electron microscope image is as follows Figure 4 As shown in the high-resolution electron microscope image Figure 5 shown.

[0085] according to Figure 2 to Figure 5 It can be seen that in the Cs1 / a-MgO / NbC composite catalyst, MgO changes from a crystalline state to an amorphous state, the composite catalyst has a sandwich-like structure, and the composite catalyst is a two-dimensional porous nanosheet.

[0086] Example 2

[0087] In this embodiment, a Cs1 / a-MgO / NbC sandwich nanocomposite catalyst was prepared. The preparation method was the same as that in Example 1, except that the Nb2AlC in step (1) was stirred in 35 mL of hydrofluoric acid solution (concentration of 60%) for 4 days.

[0088] Example 3

[0089] In this embodiment, a Cs1 / a-MgO / NbC sandwich nanocomposite catalyst is prepared. The preparation method is the same as that in Example 1, except that the Nb2AlC in step (1) is stirred in 50 mL of hydrofluoric acid solution (concentration of 60%).

[0090] Example 4

[0091] In this embodiment, a Cs1 / a-MgO / NbC sandwich nanocomposite catalyst is prepared. The preparation method is the same as that in Example 1, except that the tetrabutylammonium hydroxide solution in step (2) is replaced with a tetrapropylammonium hydroxide solution with a concentration of 25 wt%.

[0092] Example 5

[0093] In this embodiment, a Cs1 / a-MgO / NbC sandwich nanocomposite catalyst is prepared. The preparation method is the same as that in Example 1, except that the stirring time in the tetrabutylammonium hydroxide solution in step (2) is shortened or extended to 18 hours or 22 hours.

[0094] Example 6

[0095] In this embodiment, a Cs1 / a-MgO / NbC sandwich nanocomposite catalyst is prepared. The preparation method is the same as that in Example 1, except that the mass ratio of MgO to NbC in step (6) is changed from 1:10 to 1:5.

[0096] Example 7

[0097] In this embodiment, a Cs1 / a-MgO / NbC sandwich nanocomposite catalyst was prepared. The preparation method was the same as that in Example 1, except that the Cs1 / a-MgO / NbC in step (7) was replaced by + The mass ratio of NbC was changed from ~1:20 to ~1:10.

[0098] The sandwich-like nanocomposite catalysts prepared in Examples 2 to 7 are porous nanosheets, which are similar to those in Example 1 in terms of yield, morphology, size and phase structure.

[0099] Application Example 1

[0100] The Cs1 / a-MgO / NbC composite catalyst of Example 1 was used to catalyze the preparation of nitrogen-containing heterocyclic compounds.

[0101] Weigh 100 mg of the Cs1 / -a-MgO / NbC composite catalyst of Example 1 and place it in a reaction device. Add 0.5 mmol of 2-aminobenzonitrile and 3 mL of DMF solvent thereto. Exhaust the air and then fill with CO2 gas. Stir and react at a constant temperature of 100°C for 16 hours. After the reaction, filter out the solid catalyst, wash the reaction liquid adsorbed by the catalyst with dimethylformamide and dichloromethane solvent, dry it with a centrifugal concentrator, add 1,3,5-trimethoxybenzene as an internal standard, and measure the product structure and yield by nuclear magnetic resonance analysis. The yield is about 91%.

[0102] Application Example 2

[0103] The implementation steps of this application example are the same as those of application example 1, except that 2-aminobenzonitrile is replaced by 2-amino-5-fluorobenzonitrile, and the yield is 88%.

[0104] Application Example 3

[0105] The implementation steps of this application example are the same as those of application example 1, except that 2-aminobenzonitrile is replaced by 2-amino-5-bromobenzonitrile, and the yield is 79%.

[0106] Application Example 4

[0107] The implementation steps of this application example are the same as those of application example 1, except that 2-aminobenzonitrile is replaced by 2-amino-5-chlorobenzonitrile, and the yield is 76%.

[0108] Application Example 5

[0109] The implementation steps of this application example are the same as those of application example 1, except that 2-aminobenzonitrile is replaced by 2-amino-4-chlorobenzonitrile, and the yield is 69%.

[0110] Comparative Example 1

[0111] In this comparative example, a Cs1 / c-MgO / NbC sandwich nanocomposite catalyst was prepared by the same preparation method as in Example 1, except that the mixed powder obtained in step (7) was heated to 100°C in an argon atmosphere for 2 hours and then cooled naturally.

[0112] The sandwich nanocomposite catalyst prepared in this comparative example was subjected to X-ray diffraction analysis and high-resolution transmission electron microscopy. The X-ray diffraction pattern is as follows: Figure 6 As shown in the high-resolution transmission electron microscopy image Figure 7 shown.

[0113] according to Figure 6 and Figure 7 It can be seen that MgO still exists in a crystalline state.

[0114] Comparative Example 2

[0115] In this comparative example, a Na1 / a-MgO / NbC sandwich nanocomposite catalyst was prepared. The preparation method was the same as that of Example 1, except that a sodium carbonate solution was added to the MgO / NbC mixed dispersion in step (6), and the mixture was transferred to a heating device and heated to 70° C., and then heated to 90° C. and evaporated to dryness to obtain a Na-MgO-NbC mixed powder (Na + and NbC mass ratio is 1:20).

[0116] The sandwich nanocomposite catalyst prepared in this comparative example was subjected to X-ray diffraction analysis, and the results were as follows: Figure 8 As shown. Figure 8 It can be seen that the X-ray diffraction peak of Na1 / a-MgO / NbC prepared in this comparative example is mainly the diffraction peak of NbC, indicating that no impurities are introduced into the catalyst of this comparative example, Na is doped into the catalyst in ionic state, and MgO exists in an amorphous state.

[0117] Comparative Example 3

[0118] In this comparative example, a K1 / -a-MgO / NbC sandwich nanocomposite catalyst was prepared. The preparation method was the same as that of Example 1, except that potassium carbonate solution was added to the MgO / NbC mixed dispersion in step (6), and the mixture was transferred to a heating device and heated to 70° C. and then heated to 90° C. to be evaporated to dryness to obtain a K-MgO-NbC mixed powder (K + and NbC mass ratio is 1:20).

[0119] The sandwich nanocomposite catalyst prepared in this comparative example was subjected to X-ray diffraction analysis, and the results were as follows: Fig. 9 As shown. Fig. 9 It can be seen that the X-ray diffraction peak of K1 / a-MgO / NbC prepared in this comparative example is mainly the diffraction peak of NbC, indicating that no impurities are introduced into the catalyst of this comparative example, K is doped into the catalyst in ionic state, and MgO exists in an amorphous state.

[0120] Comparative Example 4

[0121] In this comparative example, a Rb1 / -a-MgO / NbC sandwich nanocomposite catalyst was prepared. The preparation method was the same as that of Example 1, except that the rubidium carbonate solution was added to the MgO / NbC mixed dispersion in step (6), and the mixture was transferred to a heating device and heated to 70° C., and then heated to 90° C. and evaporated to dryness to obtain a Rb-MgO-NbC mixed powder (Rb + and NbC mass ratio is 1:20).

[0122] Comparative Example 5

[0123] In this comparative example, an a-MgO / NbC composite catalyst was prepared. The preparation method was the same as that of Example 1, except that no Cs salt was added.

[0124] The composite catalyst prepared in this comparative example was subjected to X-ray diffraction analysis, and the results were as follows: Fig.10 As shown. Fig.10 It can be seen that the X-ray diffraction peak of a-MgO / NbC prepared in this comparative example is mainly the diffraction peak of NbC, indicating that no impurities are introduced into the catalyst of this comparative example and MgO exists in an amorphous state.

[0125] Comparative Example 6

[0126] In this comparative example, a Cs1 / NbC composite catalyst was prepared by the same preparation method as in Example 1, except that MgO nanosheets and MgO dispersion were not prepared or added.

[0127] The composite catalyst prepared in this comparative example was subjected to X-ray diffraction analysis, and the results were as follows: Fig.11 As shown. Fig.11 It can be seen that the X-ray diffraction peak of Cs1 / NbC prepared in this comparative example is mainly the diffraction peak of NbC, indicating that no impurities are introduced into the catalyst of this comparative example, and Cs is doped into the catalyst in an ionic state.

[0128] Comparative application example 1

[0129] The Cs1 / c-MgO / NbC sandwich nanocomposite catalyst of Comparative Example 1 was used to catalyze the preparation of nitrogen-containing heterocyclic compounds. The preparation steps were the same as those of Application Example 1, except that the catalyst used was Cs1 / c-MgO / NbC, the reactant molecule was 2-aminobenzonitrile, and the yield was 23%.

[0130] Comparative Application Example 2

[0131] The Na1 / a-MgO / NbC sandwich nanocomposite catalyst of Comparative Example 2 was used to catalyze the preparation of nitrogen-containing heterocyclic compounds. The preparation steps were the same as those of Application Example 1, except that the catalyst used was Na1 / a-MgO / NbC, the reactant molecule was 2-aminobenzonitrile, and the yield was 7%.

[0132] Comparative Application Example 3

[0133] The K1 / a-MgO / NbC sandwich nanocomposite catalyst of Comparative Example 3 was used to catalyze the preparation of nitrogen-containing heterocyclic compounds. The preparation steps were the same as those of Application Example 1, except that the catalyst used was K1 / a-MgO / NbC, the reactant molecule was 2-aminobenzonitrile, and the yield was 9%.

[0134] Comparative Application Example 4

[0135] The Rb1 / a-MgO / NbC sandwich nanocomposite catalyst of Comparative Example 4 was used to catalyze the preparation of nitrogen-containing heterocyclic compounds. The preparation steps were the same as those of Application Example 1, except that the catalyst used was Rb1 / a-MgO / NbC, the reactant molecule was 2-aminobenzonitrile, and the yield was 14%.

[0136] Comparative Application Example 5

[0137] The a-MgO / NbC composite catalyst of Comparative Example 5 was used to catalyze the preparation of nitrogen-containing heterocyclic compounds. The preparation steps were the same as those of Application Example 1, except that the catalyst used was a-MgO / NbC, the reactant molecule was 2-aminobenzonitrile, and the yield was 13%.

[0138] Comparative Application Example 6

[0139] The Cs1 / NbC composite catalyst of Comparative Example 6 was used to catalyze the preparation of nitrogen-containing heterocyclic compounds. The preparation steps were the same as those of Application Example 1, except that the catalyst used was Cs1 / NbC, the reactant molecule was 2-aminobenzonitrile, and the yield was 3%.

[0140] The structures and yields of the reaction products of Application Examples 1 to 5 of the present invention and Comparative Application Examples 1 to 6 were analyzed by NMR internal standard method. The comparison results are shown in Table 1.

[0141] Table 1 Yield results of application examples 1 to 5 and comparative application examples 1 to 6

[0142]

[0143]

[0144] It can be seen from Table 1 that the composite catalyst provided by the present invention not only has a high yield, even reaching 91%, but also has good universality for the reaction of organic reactant molecules with various electron-withdrawing groups with CO2 to prepare quinazolinone.

[0145] It can be seen from the above examples that the composite catalyst provided by the present invention can catalyze the preparation of nitrogen-containing heterocyclic compounds at normal pressure with high efficiency, high yield, good substrate universality, low cost, green and environmental protection, and easy separation.

[0146] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.

Claims

1. A composite catalyst, characterized in that: The invention comprises nano carbides, nano oxides and alkali metal single atoms; the nano carbides and nano oxides form a composite; the nano carbides are transition metal nano carbides; the alkali metal single atoms are loaded on the composite; the nano carbides, nano oxides and alkali metal single atoms are stacked in sequence to form a sandwich-like structure.

2. The composite catalyst according to claim 1, characterized in that The transition metal nanocarbide is niobium-based carbide.

3. The composite catalyst according to claim 1, characterized in that The nano-oxide includes crystalline nano-oxide or amorphous nano-oxide.

4. The composite catalyst according to claim 1, characterized in that The alkali metal single atom includes one or more of Na, K, Rb and Cs.

5. The composite catalyst according to claim 1, characterized in that The mass ratio of the nano-oxide to the nano-carbide is 1 to 50:100; the mass ratio of the alkali metal single atom to the nano-carbide is 0.1 to 30:

100.

6. The composite catalyst according to claim 1, characterized in that The composite catalyst is a two-dimensional porous nanosheet structure.

7. The method for preparing the composite catalyst according to any one of claims 1 to 6, characterized in that: The following steps are involved: The nano-carbide, nano-oxide, alkali metal salt and dispersion medium are mixed, evaporated to dryness and calcined in sequence to obtain the composite catalyst.

8. The preparation method according to claim 7, characterized in that: The calcination is carried out in an inert atmosphere; the calcination is programmed temperature calcination or constant temperature calcination; the temperature of the constant temperature calcination is 100-500°C, and the insulation calcination time is 1-12 hours; the programmed temperature calcination includes a first calcination, a second calcination and a third calcination in sequence; the temperature of the first calcination is 200-300°C, and the insulation calcination time is 0.5-1.5 hours; the temperature of the second calcination is 340-380°C, and the insulation calcination time is 1-3 hours; the temperature of the third calcination is 430-480°C, and the insulation calcination time is 1-3 hours.

9. Use of the composite catalyst according to any one of claims 1 to 6 or the composite catalyst obtained by the preparation method according to any one of claims 7 to 8 in catalytic preparation of nitrogen-containing heterocyclic compounds.

10. The use according to claim 9, characterized in that: The nitrogen-containing heterocyclic compound is a nitrogen heterocyclic quinazolinone compound.